Purification and characterization of recombinant Streptokinase expressed in E.coli from Streptococcus equisimilis with N-terminal methionine - Vadla, Pavan Kumar; Tummuru, Murali; Kumar, Dinesh (Jurnal Teknologi Laboratorium, 2019)
Streptokinase is a extracellular enzyme which is extracted from strains of beta Hemolytic streptococcus. The enzyme is a non-protease plasminogen activator that activates plasminogen to plasmin and degrades fibrin clot through its specific lysine binding site which is used in thrombolytic therapy. Purification of streptokinase produced from S.equisimilis in E.coli with N-terminal methionine was carried out in 3 Chromatography purification steps, 1) CM-Sepharose-FF at pH 4.2 followed by concentration and dialysis over night with Tris-HCl pH 8.0. Partially purified dialyzed enzyme sample was loaded on to 2) DEAE-Sepharose-FF column. The Purified fractions of DEAE column were pooled and applied on to Sephadex G-100 column. Enzyme purity was confirmed by SDS-PAGE and RP-HPLC.Its biological activity is determined by specific streptokinase assay and characterised the enzyme by Peptide mapping, MALDI-TOF, Isoelectric-focusing and RP-HPLC. The isoelectric point (pI) of streptokinase is around 4.98.The results of characterization shows that it contains two forms (Isomers) of streptokinase expressed in E. coli which was analyzed by RP-HPLC and chromogenic assay. The variation is formed by isomer-1 in which 85% of Streptokinase expressed without methionine (85000IU/mg) and Isomer-2 in which 15% of streptokinase expressed with methionine (nil activity) in E. coli. This phenomenon shows that the presence and absence of methionine in isomers of streptokinase varying the catalytic activity of the enzyme.